Desafíos para garantizar el derecho a la alimentación en México - Martín Díaz, Anaid Guadalupe; Espinoza Villegas, José Roberto (Journal of Behavior and Feeding, 2025)
The right to food is a fundamental human right recognized both internationally and nationally. In Mexico, guaranteeing this right faces complex challenges ranging from legal issues to the implementation of effective public policies. This article examines these challenges and proposes solutions to ensure that all Mexicans have access to adequate food. Internationally, the right to food is enshrined in several instruments, such as the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights. The Sustainable Development Goals (SDGs), specifically SDG 2, also reinforce this commitment. In Mexico, the Constitution recognizes this right, supported by federal laws such as the General Law of Social Development. Programs such as the Food Support Program (PAL) and the Social Milk Supply Program (Liconsa) aim to improve the nutrition of vulnerable populations. However, Mexico faces several challenges in ensuring this right, including poverty, inequality, and vulnerability to climate change. Food insecurity has significant implications for health, education, social cohesion, and the economy. In Mexico, health issues related to poor nutrition converge, such as malnutrition, obesity, and overweight from early ages, which affect cognitive and physical development, reducing quality of life and future opportunities. Food insecurity also perpetuates poverty and social exclusion, affecting the economic and social development of communities. In conclusion, guaranteeing the right to food in Mexico requires a constant and coordinated commitment between public policies, investment in infrastructure, and nutritional education. Only in this way can it be ensured that all Mexicans enjoy adequate, sufficient, and quality food, respecting the principles of food availability, accessibility, and stability.